2018
DOI: 10.14209/jcis.2018.27
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Criteria for Predictive Blind Deconvolution

Abstract: Blind deconvolution is a major theme in signal processing and has been intensely investigated over the last decades. Among its several applications, we can mention the problem of seismic deconvolution and channel equalization in telecommunications. In these two cases, predictive techniques have been studied by different authors, and presented satisfactory results when some suitables conditions were fulfilled. In fact, the predictive deconvolution structure, when associated with the classical mean squared error… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…for all odd, nonlinear functions (•) and (•) [1]. We also investigated in [7] the phase-response of the ℓ PEF, with ≠ 2, verifying that it can present a nonminimum phase response. However, we also observed that the ℓ PEF was not able to compensate the distortions of a channel with a generic phase response.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…for all odd, nonlinear functions (•) and (•) [1]. We also investigated in [7] the phase-response of the ℓ PEF, with ≠ 2, verifying that it can present a nonminimum phase response. However, we also observed that the ℓ PEF was not able to compensate the distortions of a channel with a generic phase response.…”
Section: Introductionmentioning
confidence: 86%
“…In [6] and [7] we have shown that the ℓ 1 PEF, with ≠ 2, performs the nonlinear decorrelation, i.e., the error signal produced has the property…”
Section: Introductionmentioning
confidence: 99%
“…In [9], we investigated how the p norms, with p = 2, can be used as alternative criteria for deconvolution. To do so, we have the following optimization problem:…”
Section: Alternative Criteria For Predictive Blind Deconvolutionmentioning
confidence: 99%
“…• For sub Gaussian distributions [14], we use p > 2, with p → ∞ for the uniform distribution. In [9] we provide a rather complete study on p criteria for predictive deconvolution, which shows that the p forward prediction error filters are able to perform the blind deconvolution of some non-minimum-phase systems. However, it still presents performance limitations according to the positions of the zeros of the channel.…”
Section: Alternative Criteria For Predictive Blind Deconvolutionmentioning
confidence: 99%
See 1 more Smart Citation